Regulating new forms of employment : local experiments and social innovation in Europe - Regalia, Ida, 1946- (Routledge/EUI studies in the political economy of welfare., 2006)
This empirically rich volume presents a comparative study of the way that new forms of work are used and becoming institutionalised in various regions in the UK, France, Germany, Italy and Spain.